Antibiotika-Forschung: Probleme und Perspektiven. Stellungnahme - Akademie der Wissenschaften Hamburg (Abhandlungen der Akademie der Wissenschaften in Hamburg, 2012)
Increasingly, antibiotic-resistant bacteria and a lack of new antibiotics to combat them are endangering the successful treatment of bacterial infections. This book describes the insufficient status quo of the development of new antibiotics and gives extensive recommendations for scientific, political and social solutions.